Projected background and sensitivity of AMoRE-II - A. Agrawal; V. V. Alenkov; P. Aryal; J. Beyer; B. Bhandari; R. S. Boiko; K. Boonin; O. Buzanov; C. R. Byeon; N. Chanthima; M. K. Cheoun; J. S. Choe; et al. (European Physical Journal C: Particles and Fields)
Abstract AMoRE-II aims to search for neutrinoless double beta decay ( $$0ν β β $$ 0 ν β β ) with an array of 423 $$\hbox {Li}_2^{100}\hbox {MoO}_4$$ Li 2 100 MoO 4 crystals operating in the cryogenic system as the main phase of the Advanced Molybdenum-based Rare process Experiment (AMoRE). AMoRE has been planned to operate in three phases: AMoRE-pilot, AMoRE-I, and AMoRE-II. AMoRE-II is currently being installed at the Yemi Underground Laboratory, located approximately 1000 m deep in Jeongseon, Korea. The goal of the experiment is to reach an exclusion half-life sensitivity to the $$0ν β β $$ 0 ν β β of $$^{100}$$ 100 Mo on the level of $$T^{0ν β β }_{1/2} > 6 × 10^{26}$$ T 1 / 2 0 ν β β > 6 × 10 26 year that covers completely the inverted Majorana neutrino mass hierarchy region of (15–46) meV. To achieve this, the background level of the experimental configurations and possible background sources of gamma and beta events should be well understood. We have intensively performed Monte Carlo simulations using the GEANT4 toolkit in all the experimental configurations with potential sources. We report the estimated background level that meets the $$10^{-4}$$ 10 - 4 counts/(keV $$· $$ · kg $$· $$ · year) requirement for AMoRE-II in the Region Of Interest (ROI) and show the projected half-life sensitivity based on the simulation study.